2015
DOI: 10.1111/jbi.12497
|View full text |Cite
|
Sign up to set email alerts
|

Genetic differentiation in the ice‐dependent fish Pleuragramma antarctica along the Antarctic Peninsula

Abstract: Aim Pleuragramma antarctica is an Antarctic notothenioid fish with a pelagic life-cycle. It plays a major trophic role in coastal Antarctic waters as a predator of krill and as prey for penguins and seals. A previous study, using mtDNA to investigate Pleuragramma population structure at multiple Antarctic sites was unable to discriminate between hypotheses of panmixia, with occasional fluctuations of allelic frequencies, and population structure. The aim of the present study was to investigate the population s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
38
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(46 citation statements)
references
References 58 publications
5
38
3
Order By: Relevance
“…This suggests that Pleuragramma from Marguerite Bay and Charcot Island are part of one contiguous population. Genetic analyses performed on fish captured in the present study yielded similar results, with the Marguerite Bay and Charcot Island fish comprising a single, panmictic population that was differentiated from the Joinville Island fish (Agostini et al, 2015). Results of those studies coupled with the results presented here provide three lines of evidence, cluster analyses, otolith microchemical analyses, and genetic analyses, that there is little connectivity between silverfish populations in the northernmost region at Joinville Island and the two southernmost regions at Marguerite Bay and Charcot Island.…”
Section: Disappearance Of Pleuragramma Antarctica From the Wap Shelfsupporting
confidence: 71%
“…This suggests that Pleuragramma from Marguerite Bay and Charcot Island are part of one contiguous population. Genetic analyses performed on fish captured in the present study yielded similar results, with the Marguerite Bay and Charcot Island fish comprising a single, panmictic population that was differentiated from the Joinville Island fish (Agostini et al, 2015). Results of those studies coupled with the results presented here provide three lines of evidence, cluster analyses, otolith microchemical analyses, and genetic analyses, that there is little connectivity between silverfish populations in the northernmost region at Joinville Island and the two southernmost regions at Marguerite Bay and Charcot Island.…”
Section: Disappearance Of Pleuragramma Antarctica From the Wap Shelfsupporting
confidence: 71%
“…This was consistent with an earlier review by Kellermann (1996), who suggested that fish spawned in the Bellingshausen Sea were advected over the western Antarctic Peninsula shelf via slope transport in the ACC. Genetics data also indicated connectivity via the AACC between silverfish found in Marguerite Bay and Charcot Island (Agostini et al 2015), which was further supported by reproductive data (La Mesa et al 2015b), otolith chemistry (Ferguson 2012), community spatial distributions (Parker et al 2015), and particle simulations based on a circulation model for the southwestern Antarctic Peninsula shelf (Piñones et al 2011). Additionally, particle simulations combined with otolith age data suggested that larvae sampled off Joinville Island were spawned in Larsen Bay in the western Weddell Sea, before being transported around the northern Antarctic Peninsula and into the Bransfield Gyre via the AACC (La Mesa et al 2015a).…”
Section: Testing Population Structure Along the Continental Shelfmentioning
confidence: 81%
“…In contrast to the AFS, the westward Antarctic Coastal Current (AACC, e.g., Moffat, Beardsley, Owens, & van Lipzig, ; Núñez‐Riboni & Fahrbach, ) is a feature typical of coastal buoyant plumes, with freshwater inputs from precipitation over the ocean, meltwater run‐off from land and sea‐ice and glacial melting (Dutrieux et al., ; Moffat et al., ). The AACC is thought to be involved in the delivery of larvae spawned in the western Weddell Sea to adult assemblages in the Bransfield Strait (La Mesa, Piñones, et al., ), and from Marguerite Bay to Charcot Island (Agostini et al., ; Ferguson, ). It is also located inshore along the Amundsen Sea, flowing around Cape Colbeck and sharply south towards the eastern Ross Ice Shelf (Orsi & Wiederwohl, ; Figure ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to heavy ice conditions and difficulties of access and sampling, the eastern Ross Sea is understudied compared to western areas. However, multi‐disciplinary approaches combining techniques that include genetics (Agostini et al., ), otolith chemistry (Ferguson, ), age distributions and circulation modelling (La Mesa, Piñones, et al., ), reproduction (La Mesa, Riginella, et al., ), and community studies (Parker et al., ) successfully tested population hypotheses along the Antarctic Peninsula. Spatial heterogeneity between discrete populations contrasts strongly to homogeneity between exported fish and their parent population, providing a useful test around which field sampling can be designed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation